(untitled) (Південний архів (історичні науки), 2022)
Purpose. The article is devoted to the analysis of scientific and pedagogical activity of the famous Odessa historian and public figure Oleksiy Ivanovych Markevich (1847–1903). Methods. The research was based on methods of criticism, analysis and evaluation of sources, archival heuristics, biographical method, historical-typological and historicalcomparative methods, the method of describing historical events. Results. As a result of the study, which is based on the analysis of historiographical, narrative and documentary sources, it was found that Alexei Markevich began teaching in the 1870s after graduating from the Faculty of History and Philology of Novorossiysk University, teaching history and Russian literature at Odessa Commercial School, Odessa Institute of Noble Girls and Mariinsky Women’s Gymnasium. From 1880 to 1895 he worked at Novorossiysk University, actively engaged in scientific work and improving his lecturing skills. Influenced by Volodymyr Antonovych’s conceptual ideas, Oleksiy Markevych laid the foundations of Ukrainian studies at Odessa University in the second half of the 19th century, prepared and gave a series of lectures on the history of Ukraine and the southern region, promoting positivist principles and populist ideas. Since 1884, the historian has been under police surveillance for his lecturing activities, and in 1895 he was dismissed from the university, officially for “health reasons”, in fact for attempting to import illegal literature from Lviv into the Russian Empire banned by the Ems Decree. Conclusions. It is concluded that scientific and pedagogical activity occupied one of the leading places in the life of Alexei Markevich. He went from private associate professor to professor at Novorossiysk University, improved his lectures on Russian history on the basis of scientific research, and for the first time in the history of the university developed and implemented training courses on the history of the southern region. His dismissal from the university interrupted his university career, but not his lectures. Until the end of his life he remained a brilliant teacher and orator, working as a lecturer in public auditoriums and speaking at public readings.